2001
DOI: 10.1002/lsm.1106
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways involved in low intensity He–Ne laser‐induced respiratory burst in bovine neutrophils: A potential mechanism of low intensity laser biostimulation

Abstract: These results suggest that PTKs play a key role in the He-Ne laser-induced respiratory burst of neutrophils and [PTK-PLC-PKC-NADPH oxidase] signal transduction pathways may be involved in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…For example, LEVL increases the rate of wound healing (3), enhances the fertilizing capability of sperm cells (4), and increases the rate of healing bone defects (5). In vitro studies have found that LEVL increases proliferation of cells as fibroblasts (6), keratinocytes (7), and lymphocytes (8) and induces the respiratory burst in neutrophils (9). The mechanism of photobiostimulation by LEVL is still unclear.…”
mentioning
confidence: 99%
“…For example, LEVL increases the rate of wound healing (3), enhances the fertilizing capability of sperm cells (4), and increases the rate of healing bone defects (5). In vitro studies have found that LEVL increases proliferation of cells as fibroblasts (6), keratinocytes (7), and lymphocytes (8) and induces the respiratory burst in neutrophils (9). The mechanism of photobiostimulation by LEVL is still unclear.…”
mentioning
confidence: 99%
“…Thus, CINN did not directly attenuate the MPO pathway. In previous studies, calphostin C, an inhibitor of protein kinase C (PKC) can obviously reduce the He-Ne laser-induced respiratory burst of neutrophils [32], and the PMA is a stimulator for PKC-mediated NADPH oxidase and nitric oxide (NO) synthase during respiratory burst of neutrophils [33]. Therefore, it was very possible that CINN could also be a PKC inhibitor, It should be emphasized that fluorescent dyes such as DHR (for H 2 O 2 ) and DHE (for superoxide radical) is not the best method of choice for radical detection, although it is more preferable in the cellular-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…TPKR affect also cell proliferation by the Phosphatidylinositide 3-kinases (PI3K)/Protein kinases B (Akt) pathway and Phospolipase C gamma (PLC-gamma)/Protein kinases C (PKC) pathway [7]. ROS produced as a cellular response to irradiation of LLLT, activates Src tyrosine kinase [8], which is responsible for increased proliferation of many kinds of cell cultures.…”
Section: Modification Of Kinases Activitymentioning
confidence: 99%